Association between NF-κB Activation in Peripheral Blood Mononuclear Cells and Late Skin and Subcutaneous Fibrosis following Radiotherapy. (21st July 2020) - Su, Yapin; Zhang, Yuyu; Sun, Meiting; Liu, Wenhui; Pei, Fengli; Han, Fujun
Abstract : Background . This study aimed at evaluating the association between the speed of nuclear factor-kappa B (NF- κ B) activation in peripheral blood mononuclear cells (PBMCs) and late skin and subcutaneous fibrosis in patients with head and neck squamous cell carcinoma (HNSCC) after radiotherapy. Methods . The speed of NF- κ B activation was represented by the nuclear p65 expression ratio before and after irradiation. The optimal time point to measure the ratio was determined by Western blot in the PBMCs from healthy outpatients ranging from 0 to 12 hours after ex vivo irradiation. We recruited patients with HNSCC who had received ratiotherapy and who were under regular follow-up care. We assessed the association between the risk of developing ≥grade 2 late fibrosis and the nuclear p65 expression ratio in the PBMCs after ex vivo irradiation in these patients. Results . The maximum nuclear p65 ratio was observed at 1 hour after ex vivo irradiation in the PBMCs from the healthy outpatients. The speed of NF- κ B activation was then represented by the nuclear p65 ratio in the PBMCs before and 1 hour after ex vivo irradiation. A total of 200 patients with HNSCC were recruited, 32.50% (n = 65 ) of which presented with ≥grade 2 late fibrosis. There was a significant association between the speed of NF- κ B activation in the PBMCs and an increased risk of developing ≥grade 2 late fibrosis in these patients (P = 0.004 ). Subgroup analysis suggested that this finding was independent of the known clinical characteristics. Conclusions . The speed of NF- κ B activation might be a potential predictor of late toxicity in cancer patients after radiotherapy. Prospective studies are needed for validation.